2001
DOI: 10.1073/pnas.071613498
|View full text |Cite
|
Sign up to set email alerts
|

Reciprocal electromechanical properties of rat prestin: The motor molecule from rat outer hair cells

Abstract: Cochlear outer hair cells (OHCs) are responsible for the exquisite sensitivity, dynamic range, and frequency-resolving capacity of the mammalian hearing organ. These unique cells respond to an electrical stimulus with a cycle-by-cycle change in cell length that is mediated by molecular motors in the cells' basolateral membrane. Recent work identified prestin, a protein with similarity to pendrin-related anion transporters, as the OHC motor molecule. Here we show that heterologously expressed prestin from rat O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
119
0
2

Year Published

2002
2002
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 150 publications
(129 citation statements)
references
References 34 publications
8
119
0
2
Order By: Relevance
“…The experimental topology data presented here is the first to be reported for SLC26A3 and supports a model with intracellularly located N and C termini. Consistent with our results, some previous studies on SLC26A5 and SLC26A6 have indicated that the N and C termini of these proteins are located in the cytosol (7,10,13,61). The location of the N terminus is important as previous reports have reported it to be proteolytically cleaved in vivo (65,66), raising the possibility that proteolytic cleavage may regulate transporter function.…”
Section: Discussionsupporting
confidence: 81%
“…The experimental topology data presented here is the first to be reported for SLC26A3 and supports a model with intracellularly located N and C termini. Consistent with our results, some previous studies on SLC26A5 and SLC26A6 have indicated that the N and C termini of these proteins are located in the cytosol (7,10,13,61). The location of the N terminus is important as previous reports have reported it to be proteolytically cleaved in vivo (65,66), raising the possibility that proteolytic cleavage may regulate transporter function.…”
Section: Discussionsupporting
confidence: 81%
“…Prestin (SLC26A5) (14) is a motor protein specific to cochlear outer hair cells and thought to be responsible for active mechanical amplification in mammalian ears (6)(7)(8)(9). Beside prestin, pendrin (SLC26A4) (15) is a member of the SLC26 family, displaying a defined expression pattern in the developing cochlea different from that of prestin.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5]. A molecular motor driving this cellular electromotility has been identified recently to be prestin, a membrane-based molecule that seems to change its conformation in a voltage-dependent way (6)(7)(8)(9).…”
mentioning
confidence: 99%
“…Whole-cell patch-clamp recordings were performed to determine NLC of: 1) OHCs mechanically isolated from the adult guinea-pig cochlea, and 2) HEK293 cells transfected with plasmids encoding prestin [8]. OHCs were bathed in Hanks' balanced salt solution (HBSS, pH 7.3, osmolarity 310 mOsm/L).…”
Section: Methodsmentioning
confidence: 99%